2015
DOI: 10.1038/srep11808
|View full text |Cite
|
Sign up to set email alerts
|

Detection of UV-induced cyclobutane pyrimidine dimers by near-infrared spectroscopy and aquaphotomics

Abstract: Ultraviolet (UV) radiation causes cellular DNA damage, among which cyclobutane pyrimidine dimers (CPDs) are responsible for a variety of genetic mutations. Although several approaches have been developed for detection of CPDs, conventional methods require time-consuming steps. Aquaphotomics, a new approach based on near-infrared spectroscopy (NIRS) and multivariate analysis that determines interactions between water and other components of the solution, has become an effective method for qualitative and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Furthermore, CXCL1, a neutrophil attractant chemokine, is significantly upregulated in the blood serum of Xpa-knockout mice after UVB exposure and once the neutralizing antibody against CXCL1 was administered at every exposure of UVB, the number of developed skin tumors in Xpa-knockout mice actually decreased (8). Long-term use of the diuretic agent hydrochlorothiazide (HCTZ), another photosensitizing drug, was associated with an increased risk of nonmelanoma skin cancer (10,11) and we previously showed that HCTZ enhanced the formation of CPD after UVA irradiation (12). Taken together, the abnormal photosensitized skin inflammation caused by voriconazole or HCTZ may play a role in the development of nonmelanoma skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CXCL1, a neutrophil attractant chemokine, is significantly upregulated in the blood serum of Xpa-knockout mice after UVB exposure and once the neutralizing antibody against CXCL1 was administered at every exposure of UVB, the number of developed skin tumors in Xpa-knockout mice actually decreased (8). Long-term use of the diuretic agent hydrochlorothiazide (HCTZ), another photosensitizing drug, was associated with an increased risk of nonmelanoma skin cancer (10,11) and we previously showed that HCTZ enhanced the formation of CPD after UVA irradiation (12). Taken together, the abnormal photosensitized skin inflammation caused by voriconazole or HCTZ may play a role in the development of nonmelanoma skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Tsenkova has defined 12 characteristic water wavelength ranges which cover various conformations of water molecules and are very useful to present water spectral pattern [18]. The ranges of WAMACs were defined as follows: C1 (1336- [18,26]. Figure 6 shows the aquagrams of the hydrogel contact lenses representing the average of the pretreated spectra of the individual lenses across all replicas and experiments, at selected 12 characteristic water wavelengths from the WAMACs regions.…”
Section: Resultsmentioning
confidence: 99%
“…These water bands, called WAMACs [18], originate from the different water molecular conformations such as free water molecular species, water dimers, trimers, tetramers, or pentamers. Aquaphotomics approach was so far applied for various detection, qualitative descriptions, quantification, dynamic monitoring, and diagnostic purposes [18,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, formation of CDPs is cause of UV-induced cytotoxicity and mutagenicity, playing an important role in photocarcinogenesis [ 41 ]. In this work, CPDs evaluation confirmed that the low doses of UVA/UVB used to stimulate fibroblasts did not induce detectable damage.…”
Section: Discussionmentioning
confidence: 99%